"Ignoramics" in Medical and Premedical Education. (1st October 2008) - Witte, Marlys H.; Crown, Peter; Bernas, Michael; Garcia, Francisco A.R.
Abstract : As physician-essayist Lewis Thomas has urged, ignorance-based courses and curricula are urgently needed in medical education to prepare future generations of scientific physicians and physician-scientists for the uncertain, rapidly changing world ahead. This article reviews the evolving concept of ignorance in general and specifically in medicine and its relationship to knowledge. Issues about goals, content, and assessment of such ignorance-based courses are discussed along with the experience of the University of Arizona's National Institutes of Health-sponsored Summer Institute on Medical Ignorance for medical student researchers and disadvantaged high school students. Summer Institute on Medical Ignorance activities can be readily replicated or adopted in their entirety or partially in both live and Internet-based formats. These will serve to introduce medical ignoramics and questioning as a way to balance the information-overloaded medical curriculum.